Exploring Maze Navigation: A Comparative Study of DFS, BFS, and A Search Algorithms - ELKARI, Badr; OURABAH, Loubna; SEKKAT, Hiba; HSAINE, Ayoub; ESSAIOUAD, Chama; BOUARGANE, Yassine; El Moutaouakil, Karim (Statistics, optimization & information computing, 2024)
A comparative study was conducted using Python and Pmaze to evaluate the performance of DFS, BFS, and A* search algorithms in path planning for a maze. The main objective of the project was to compare the efficiency of these algorithms in terms of path cost and algorithmic complexity. No physical robot was used in this study as it focused solely on the analysis of search algorithms. This study contributes to the advancement of knowledge in the field of path planning by exploring different approaches for mazes using Python and Pmaze.